Economic Freedom, Macroeconomic Fundamentals and Foreign Direct Investment in Fast Emerging Brics and Malaysia (International Journal of Banking and Finance, 2013)
This study investigates the major factors that determine the inflow of foreign direct investment (FDI) into fast emerging countries: Brazil, China, India, Russia, South Africa (BRICS) and Malaysia. Two sets of factors are identified: macroeconomic and country specific fundamentals. The period of analysis is 1977-2010. The study provides empirical evidence that economic growth, government consumption and trade openness are vital for FDI. In addition, country specific infrastructure quality and economic freedom are also critical factors in determining FDI for this group of countries. Our findings have significant policy implications for the growth and development of these countries, particularly through foreign direct investments.